EVOLUTION OF MOUNTAIN LAKES, GENETIC CLASSIFICATIONS, AND SPECIFIC FEATURES (Scientific journal of the Fergana State University, 2025)
Mountain lakes are widespread in all mountain regions of the Earth. They vary significantly from each other in their origin (genesis), as well as in the shape and size of their lake basins. This is primarily because, with increasing altitude in mountain areas, natural conditions (including geological, geomorphological, hydrometeorological) and the ongoing natural-geographical processes (denudational, gravitational, hydrological, hydrogeological, glaciogenic, fluvioglacial, and others) manifest in diverse ways. In connection with this, this article analyzes the formation conditions, evolution, genetic classifications, and specific features of mountain lakes.